Multiple Structural Breaks in Profit Share Rates of Participation Banks in Turkey: Are They Caused by the Recent Global Crises? - Mehmet Levent Erdas (Türkiye İslam İktisadı Dergisi)
The global crises not only affect the economy of the country in which they emerge but also spread to other countries. Economic growth and stability levels will inevitably be affected by these crises especially in devel- oping countries. To this end, the aim of this study is to identify the multiple structural breaks in profit share rates by employing the methodology developed by Bai and Perron (1998, 2003a) and Liu et al. (1997). I used the monthly data covering the period 1998-2018 for the estimated structural break dates. The results of the analysis indicate that there is at least one breakpoint in the time series of the analysed profit share rates. The identified break dates obtained within the study confirm the periods affected by the global crises in 2000-2001 and 2007-2008. Under those results, it is revealed that the participation banks have been exposed to structural changes at various times and it may be emphasized that the profit share rates have become more deteriorated to changes in the global fi- nancial market.